Artificial genetic code of development of electric power system - Tchórzewski, Jerzy (Studia Informatica. System and information technology, 2019)
The paper presents the results of research concerning the identification of electric power system development, which was carried out for the IEEE RST 96 test data [4, 13]. The problem of development was formulated in the form of artificial genetic code, and the results of the research concerning the regularities of the development of the electric power system on the basis of IEEE RST 96 test data, including the obtained coefficient-based artificial code of development.